Environmental Psychology – psychological motivation towards pro-environmental behavior - Chintarra Fariska Rizanti; Ratna Djuwita (Jurnal Impresi Indonesia, 2025)
Climate change and environmental degradation require effective solutions to promote pro-environmental behavior. This kind of behavior tends to be caused by social norms, personal values, environmental awareness, and emotions. Using a systematic literature review (SLR) approach, this paper analyzes seven articles to explore the role of psychological motivation in promoting sustainability. The findings suggest that social norms can stimulate collective action, while personal values and environmental awareness reinforce individual motivation. Positive emotions such as pride, and negative feelings such as guilt, help in the commitment to sustainability. In the Indonesian context, cultural practices such as "gotong royong" can be integrated into community-based policies and programs to increase community involvement in pro-environmental behavior. This paper concludes that a variety of strategies that leverage psychological motivations, local values, and emotions may be applicable in promoting sustainability with an emphasis on Indonesia.